1985
DOI: 10.1128/jcm.22.3.352-354.1985
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas pseudomallei infection from drowning: the first reported case in Taiwan

Abstract: We report a case of Pseudomonas pseudomallei infection, in which the patient acquired the bacteria by aspiration of river water after a drowning incident near Manila, the Philippines. The pulmonary form of melioidosis was noted at the onset, but septicemia developed at a later stage. Positive blood cultures were obtained 17 days after the accident. The patient was treated successfully with a combination of amikacin and cephalothin. This is the first report of P. pseudomallei infection documented in Taiwan. Mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…16 Onset of melioidosis within 24 hours has been seen in presumed aspiration after neardrowning and, in some cases, after severe weather events. 98,99 Bacteremia on admission occurs in 40 to 60% of the cases, septic shock in around 20% and pneumonia is the presenting illness in over half of all cases. Mortality rates overall are currently between 10% in Australia and 40% in Thailand, 21 with still higher rates in resource-poor areas where access to diagnosis and therapy are limited.…”
Section: Clinical Manifestations: Enormous Diversity But Pneumonia Prmentioning
confidence: 99%
“…16 Onset of melioidosis within 24 hours has been seen in presumed aspiration after neardrowning and, in some cases, after severe weather events. 98,99 Bacteremia on admission occurs in 40 to 60% of the cases, septic shock in around 20% and pneumonia is the presenting illness in over half of all cases. Mortality rates overall are currently between 10% in Australia and 40% in Thailand, 21 with still higher rates in resource-poor areas where access to diagnosis and therapy are limited.…”
Section: Clinical Manifestations: Enormous Diversity But Pneumonia Prmentioning
confidence: 99%
“…Possibly the first such case was described in 1948 66, and several subsequent reports have suggested that infection was probably contracted in the Philippines (55,73,74,94,126,169), although in individuals who have travelled extensively within endemic areas it is often impossible to be certain as to the origin of infection.…”
Section: History and Geographical Distributionmentioning
confidence: 99%
“…B. pseudomallei is also a major cause of community-acquired septicemia and pneumonia in adults in the Asia-pacific region, particularly in northeast Thailand (Peto et al, 2014 ). In Taiwan, the first case of melioidosis was reported in 1985 in a man who acquired the disease after aspirating river water in a near-drowning accident in the Philippines (Lee et al, 1985 ) Since then several sporadic and epidemic cases have been reported (Hsueh et al, 2001 ; Ko et al, 2007 ; Su et al, 2011 ; Chen et al, 2013 , 2014 ). Previous studies clearly showed that the disease was endemic in Taiwan and demonstrated that all clinical isolates were arabinose non-assimilators (Hsueh et al, 2001 ; Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%